FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA - Marissa Putriana (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
This study was conducted to examine the effect of variables Working Capital to Total Assets (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Assets Turnover (TAT), Net Profit Margin (NPM) and Gross Profit Margin (GPM) on the growth of earnings. Data obtained by the method of purposive sampling criteria: (1) companies incorporated in LQ45 2005-2015 period, (2) companies that are engaged in services, (3) and during the study period these companies do not generate profits the negative. The analysis showed that the data used in this study have met the classical assumptions, which include: no symptoms of multicollinearity, there is no autocorrelation, no symptoms occur heteroskedastisitas, and normally distributed data. From the results of regression analysis showed that the variable Operating Income to Total Assets (OITL) and Net Profit Margin (NPM) partially significant effect on earnings growth. While the variables Working Capital to Total Assets (WCTA), Current Liabilities To Inventory (CLI), Total Assets Turnover (TAT), and Gross Profit Margin (GPM) no significant effect on earnings growth. The six variables used in this study (WCTA, CLI, OITL, TAT, NPM and GPM) simultaneously no significant effect on earnings growth, with the predictive capabilities of the six variables of 20.7%. Keywords: Working Capital to Total Assets (WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total Assets Turnover (TAT), Net Profit Margin (NPM), Gross Profit Margin (GPM) and profit growth.